Pengaruh Perilaku Masyarakat dan Container Indeks Terhadap Kejadian DBD di Puskesmas Sumbawa Unit II - Salsawina Chalista, Putri; Hamid, Abdul; Arifatus Sholihah, Nur (Pustaka Galeri Mandiri, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia, especially in tropical regions such as Sumbawa District. This study aims to determine the influence of community behavior and Container Index (CI) on the incidence of DHF in the working area of Sumbawa Unit II Health Center. This quantitative research employed an analytic observational design with a cross-sectional approach. A total of 132 households were selected using purposive sampling. Data were collected through questionnaires and field observations, and analyzed using multiple linear regression with IBM SPSS version 29.0. The results showed that community behavior related to 4M Plus activities (p<0.05), clothes-hanging habits (p<0.05), and Container Index (p<0.05) significantly affected the incidence of DHF. It can be concluded that community behavior and environmental conditions play an important role in the transmission of DHF. Strengthening health education, regular vector monitoring, and environmental management are recommended to reduce DHF incidence in endemic areas